Advances in computer algebra : in honour of Sergei Abramov's' 70th birthday, WWCA 2016, Waterloo, Ontario, Canada /: in honour of Sergei Abramov's' 70th birthday, WWCA 2016, Waterloo, Ontario, Canada. (2018) - Unknown
No abstract available